2019
DOI: 10.1002/adfm.201900819
|View full text |Cite
|
Sign up to set email alerts
|

Beetle‐Inspired Assembly of Heterostructured Lamellar Membranes with Polymer Cluster–Patterned Surface for Enhanced Molecular Permeation

Abstract: 2D lamellar membranes hold great promise in efficient molecular separations of liquid and gas mixtures. However, the simultaneous realization of high permeation and precise sieving (i.e., overcoming the permeation-rejection tradeoff ) of membranes poses a great challenge. Inspired by the structures and functions of the beetle's back, the heterostructured lamellar membranes fabricated through facile and controllable electrostatic atomization method are reported. Particularly, hydrophobic polymer clusters are pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…The favorable dissolution property of the DAN outer coating and the fast diffusion through the PDMS inner coating co‐contribute to the result of highly efficient toluene transport. Figure 7(b) summarizes the performances of OSN membranes in literature 24,26,27,37–39 . OSN membranes with the double coating structure prepared in this study bring prominent improvement to solvent permeance and selectivity.…”
Section: Resultsmentioning
confidence: 95%
“…The favorable dissolution property of the DAN outer coating and the fast diffusion through the PDMS inner coating co‐contribute to the result of highly efficient toluene transport. Figure 7(b) summarizes the performances of OSN membranes in literature 24,26,27,37–39 . OSN membranes with the double coating structure prepared in this study bring prominent improvement to solvent permeance and selectivity.…”
Section: Resultsmentioning
confidence: 95%
“…As the novel two-dimensional materials developed, twodimensional (2D) membranes can be exploited as competitive candidates for OSN applications. 15,16 The two-dimensional separation membrane consists of several layers of nanosheets stacked parallel to each other with atomic layer thickness. 17,18 Because of the voids between adjacent nanosheets, this unique structure results in uniform performance of transmission and separation.…”
Section: Introductionmentioning
confidence: 99%
“…2015 , 2019 ; Yang et al. 2017 , 2019a , 2019b ; Li et al., 2013 ; Wang et al., 2019a ; Wu et al., 2020 ; Song et al., 2017 ). Theoretical calculations showed that single-layered nanoporous GO membranes could achieve ultrafast molecule sieving ( Cohen-Tanugi and Grossman, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the unique atomic thickness, extraordinary physicochemical properties, and micrometer lateral dimensions, numerous attempts are made for providing the foundation in fabricating highly permeable graphene oxide (GO) membranes, which deposits a GO film on an ultrafiltration or a microfiltration membrane support (Mi 2014;Zhang et al 2015Zhang et al , 2019Yang et al 2017Yang et al , 2019aYang et al , 2019bLi et al, 2013;Wang et al, 2019a;Wu et al, 2020;Song et al, 2017). Theoretical calculations showed that single-layered nanoporous GO membranes could achieve ultrafast molecule sieving (Cohen-Tanugi and Grossman, 2012).…”
Section: Introductionmentioning
confidence: 99%